THE ROLE OF NEEDS ANALYSIS IN CRAFTING ENGLISH LANGUAGE CURRICULA FOR GENERAL DUTY NURSING STUDENTS AT ISTM KINSHASA - Bemba, L; Tshibangu, M (Research Journal of Literature, Languages and Linguistics, 2024)
Assessing the needs of learners is an essential step in designing an appropriate syllabus that takes into account the real needs of students. This study aimed to investigate the English learning needs of ISTM Kinshasa general duty nursing students, using a qualitative approach and triangulated sources of data including students, current nurses, experienced content teachers, and the head of nursing section. The data were analyzed using a coding system that produced frequency scores of categories for the four sources. The findings revealed that the main topics to include in the English course content for general duty nursing are identification of people, departments, equipment, and objects in a hospital; contextualized key medical terms for professional communication; and basic general English knowledge. These topics are relevant not only for ISTM Kinshasa general duty nursing students but also for other nursing students with slight modifications. The study highlights the importance of collaboration between English language teachers and content specialists in designing course content that meets the needs of learners and that helps them develop the four language skills in nursing context. The findings also emphasize the need for a periodic review of the syllabus to ensure its relevance to the dynamic needs of the learners.